Estudo da precisão da técnica de cirurgia guiada para instalação de implantes em maxilas e mandíbulas edêntulas - Vieira, Dalton Marinho (2009)
The aim of this study was to compare the level of technical accuracy of the guided surgery for the installation of implants in completely edentulous maxilla and mandible using the Dental Slice software. Material and Methods: five mandibles and five maxillae were compared in this study, checking the linear and angular dispersion of the installed implants. Patients had the following requirements for this study: totally edentulous maxillae and / or mandible; mouth opening of at least 50mm, good health condition, alveolar ridge with the minimum thickness of 5mm and height of 10mm. After screening, undergoing clinical exams and radiographic and panoramic tomography, moldings were performed in order to obtain the samples for the assembly in the semi-adjustable articulator (Bio Art). After assembling the teeth in wax, tests and adjustments were made in the mouth. After that, the duplication of the waxing with incol or autopolimerizable resin for the preparation was carried out. With the tomographic guide, six perforations with spherical drills number 8 with a maximum diameter of 1mm by 1mm in depth, adding gutta-percha, were made. An occlusal record of condensation silicone was obtained. Two tomographies were performed with cuts of 0.2 mm in thickness: one with a guide and with a positioned occlusal record and the other with only the tomographic guide, superimposing the two images after this. The data were stored in DICOM extension and recorded on a CD. After the conversion to the specific software, the virtual surgical and prosthetic planning was made. Results: It was found that the largest discrepancies were found in the apical third of the implants. These discrepancies had intermediate values in the middle third and lower values in the coronal third. Angular and linear Discrepancies were bigger in the maxilla compared to the mandible in the three analyzed thirds. The comparison of overall average deviation angle was 2.1536 ± 0.6801 for the maxilla and 0.6505 ± 1.6607 for the mandible. The angular deviations between the coronal third, middle and apical showed no statistical differences when individually analyzed for the mandible and maxilla. The difference in averages of apical deviation is 1.0879 ± 0.4508 for mandible and 2.7125 ± 1.8367 for maxilla. A comparison of the coronal medium is 1.0332 ± 0.4840 for mandible and 2.3192 ± 1.0893 for maxilla. A comparison of the average of the middle third is 1.0421 ± 0.4621 ± 2.3293 in the mandible and 1.3248 in maxilla. The lower deviation is the coronal, following the medium and then the apical, both in the maxilla and in the mandible. These values showed statistically significant differences for p <0.05 between them. Linear deviations in the maxilla and mandible showed no significant statistical results at the level of p <0.5 for the maxilla and p <0.8 for the mandible. Conclusions: The deviations obtained in the maxilla and mandibles are considered minimal, compared to implants placed in the virtual model and clinically implemented. The angular and linear deviations were smaller in the mandible than in maxilla. The angular and linear discrepancies were smaller in the coronal third relating to the middle third and apical. The surgery for the installation of computer-guided flapless implant was considered, through this work, as being a feasible and safe technique.